Contrastes da modernidade na obra "Drácula" de Bram Stoker - Sotoriva, Franciele Gleice (2017)
This work aims to understand how the work "Dracula of Bram Stoker" presents modernity and its counterpoint to the traditional. This horror novel was written in the late nineteenth century (1897), at a period of many technological innovations resulting from the Industrial Revolution, such as the expansion of railways, the invention of the telephone, the phonograph, advances in knowledge of physics, chemistry, mathematics and biology, or even the use of electricity. These changes are present in the work, so the author cites throughout the text the use of modern scientific methods for the period, such as blood transfusion, hypnotism, fast transport and shorthand. "Dracula" was written in London, the greatest development pole of the time, where the Industrial Revolution first took place and where technological innovations were more evident, which inserted the author in a context of transformations that became perceptible in his writing. In century XIX constituted the Victorian era in England, the period referring to the reign of Queen Victoria, from 1837 to 1901. English society was moralistic, puritanical, traditionalist until then, and "Dracula" comes in opposition to this as well, as a criticism to show that new times are emerging. Stoker's work has a positive view of modernity and science, as it uses the characters linked to knowledge (doctor, scientist, lawyer) as the positive poles of the novel. In relation to the villain Count Dracula, this represents the traditional and at the same time the old, the perdition, the promiscuity, which in a certain way reflects the author's attitude towards the duality then existing between those who believed that science was something positive and those who criticized her as a threat. Literature is something instigating for the study in history, opening up numerous possibilities for analysis. We emphasize, through this case study, the importance that the literary genre has for historical research.